Efficacy and Safety of Lenvatinib Combined With PD-1 Inhibitors Plus TACE for Unresectable Hepatocellular Carcinoma Patients in China Real-World - Li, Xiaowei; Fu, Zhigang; Chen, Xiaoxia; Cao, Kunkun; Zhong, Jiaming; Liu, Li; Ding, Ning; Zhang, Xiaoli; Zhai, Jian; Qu, Zengqiang (Frontiers in Oncology, 2022)
To evaluate the efficacy and safety of lenvatinib combined with programmed death receptor-1 signaling inhibitors plus transarterial chemoembolization (LePD1-TACE) for treatment of unresectable hepatocellular carcinoma (uHCC) in a real-world setting in China. Methods: This was a retrospective study involving consecutive patients with uHCC (n =114) receiving LePD1-TACE treatment from June 2019 to May 2021. Overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and DCR were calculated to evaluate the antitumor efficacy. Treatment-related adverse events (TRAEs) were analyzed to assess the safety profiles. In addition, we also evaluated prognostic factors related to survival and disease progression. Results: A total of 114 patients with a median age of 53 years were analyzed during a median follow-up duration of 10.6 months (95% CI: 8.5 -12.8). The Kaplan-Meier analysis showed that the median OS was 18.0 months (95% CI: 14.1 - Not reached), the median PFS was 10.4 months (95% CI: 6.6 - 12.4). Based on modified Response Evaluation Criteria in Solid Tumors, the best ORR was 69.3% and DCR was 80.7%. Almost all patients suffered from TRAEs, the most common grade 3-4 TRAEs were hypertension (8.8%), proteinuria (3.6%), hyperbilirubinemia (1.8%), leukopenia (4.4%) and alanine aminotransferase elevation (3.6%) across all patients. The independent treatment factors associated with OS and PFS were tumor number, NLR and the early tumor response. In the early tumor response (CR+PR) patients, median OS and PFS were 25.1 months (95% CI: 13.8 - NA) and 15.2 months (95% ACI: 10.5 - 19.1). The patients with tumor number < 3 had a superior median OS and PFS (25.1, 16.4 months) compared to patients with tumor number ≥ 3 (14.1 months, P = 0.012; 6.6 months, P = 0.007). The patients with NLR ≤ 2.165 had a longer median OS and PFS (Not reached, 15.2 months) than those with NLR > 2.165 (17.7 months, P = 0.003; 7.5 months, P = 0.047). Conclusion: In this real-world study, LePD1-TACE triple therapy showed encouraging efficiency and manageable safety in patients with uHCC. The tumor number (< 3), NLR (≤ 2.165) and early tumor response (CR+PR) could be one of the prognostic markers.